Credit and Saving Constraints in General Equilibrium : A Quantitative Exploration (2019)
ABSTRACT: In this paper we build an incomplete-markets model with heterogeneous households and firms to study the aggregate effects of saving constraints and credit constraints in general equilibrium. We calibrate the model using survey data from Colombia, a developing country in which informal saving and credit frictions are pervasive. Our quantitative results suggest that reducing savings costs increases selection into formal saving, but the effect on aggregate outcomes and welfare is dwarfed by that of a policy which ameliorates borrowing constraints. Such a policy improves resource allocation and increases returns to capital and labor, resulting in higher savings and welfare gains for both households and firms.